Risk Factors for Development of Biliary Complications after Surgery for Solitary Liver Hydatid Cyst. Issue 1 (January 2017) - Surmelioglu, Ali; Ozer, Ilter; Reyhan, Enver; Dalgic, Tahsin; Ozdemir, Yilmaz; Ulas, Murat; Bostanci, Erdal B.; Akoglu, Musa
Biliary leakage (BL) is the most common cause of postoperative morbidity after conservative liver hydatid cyst surgery. The objective of this study was to determine incidence of BL and related risk factors in patients with solitary liver hydatid cyst who underwent conservative surgery. A total of 186 patients were included in this study. Age, gender, cyst recurrence, diameter, and localization, World Health Organization Informal Working Group on Echinococcosis (WHO-IWGE) classification, cavity management techniques, cyst content, and alkaline phosphatase (ALP) levels were evaluated with univariate and multivariate analyses. Of these patients 104 were female and 82 were male. The mean age was 43.5 ± 14.7 years. Postoperative BL was detected in 36 (19.4%) patients. Cyst diameter (P = 0.019), cyst localization (P = 0.007), WHO-IWGE classification (P = 0.017), and ALP level (P = 0.001) were the most significant risk factors for BL. Independent risk factors for BL were perihilar localization, large cyst diameter, high ALP level, and advanced age according to WHO-IWGE classification.